PERLINDUNGAN HUKUM TERHADAP PETUGAS LEMBAGA PEMASYARAKATAN DALAM PELAKSANAAN TUGAS PENGAMANAN PADA LAPAS KLAS IIA PADANG - M.H, Ernawati (Universitas Ekasakti, 2019)
Legal protection against Correctional Officers in carrying out security duties is based on Law No. 12 of 1995 concerning Correctional Services. Given the risks posed by security duties at Correctional Institutions, the Security Officers need to be given legal protection so that the aims and objectives of implementing security tasks can be achieved. which in turn the correctional goals themselves can be realized. With such a background, there are two main problems in implementing legal protection against correctional officers, namely: First What is the legal protection of Correctional Officers in the implementation of security duties at the Padang Class IIA Correctional Institution? Second What are the Constraints of Constraints encountered in the Implementation of Legal Protection for Correctional Officers in the Implementation of the Duty of Security at the Padang Class IIA Correctional Institution? The implementation of legal protection in terms of answering the existing problems, which is seen in the implementation in Padang Class IIA Lapas can be understood that the legal protection of correctional officers in Lapas Klas IIA Padang is carried out based on legal provisions regarding correctional facilities. In this case Padang Class IIA Lapas provides legal protection to correctional officers in carrying out security duties carried out in accordance with applicable legal rules concerning correctional duties and legal rules regarding security itself. The rule of implementative law regarding correcting about safeguards refers to legal rules regarding correctional codes of ethics and legal rules concerning the security of prisons regulated in Permenkumham Number M.HH-16.KP.05.02 of 2011 concerning the Code of Conduct for Correctional Staff and Permenkumham No. 33 of 2015 concerning Security at Penitentiary Institutions and State Detention Houses. The implementation of legal protection against correctional officers in carrying out security duties is carried out based on these legal rules, so that legal protection for correctional officers can be provided in the event that correctional officers carry out security duties based on applicable legal rules.